Disseminated classic Kaposi's sarcoma associated with human herpesvirus 8 infection - Poljački, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
Authors report a case of disseminated form of classic Kaposi's sarcoma case, in which presence of DNA sequences of human herpesvirus 8 has been confirmed. Viral DNA was identified with nested PCR method in tissue samples of skin and tumor of left submandibular region. Detected sequences corresponded to amplicone of 160 base pairs. In accordance with previous literature reports, these results confirm the possible etiopathogenetic role of Human herpesvirus 8 in classic Kaposi's sarcoma development.
Keywords: Aged; Dna, viral; Herpesvirus, kaposi's sarcoma-associated; Polymerase chain reaction; Sarcoma, kaposi's